2020
DOI: 10.24815/jdab.v7i2.17150
|View full text |Cite
|
Sign up to set email alerts
|

Green Banking and Performance: The Role of Foreign and Public Ownership

Abstract: This study aims at examining the effect of green banking practice on bank performance with foreign and public ownerships as moderating variables. Data were collected from 14 Indonesian banking or 98 bank-year observations. The sample banks were participated in the green banking pilot project and listed in investasi hijau (or green investment) index between 2012 and 2018. Using the ordinary least square (OLS) model, this study demonstrates that green banking practices have a negative impact on bank profitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
2
8
0
6
Order By: Relevance
“…Khan et al (2021) showed that the disclosure of green banking has a positive and significant effect on the value of companies. Karyani and Obrien (2020), Bose et al (2021), and Park and Kim (2020) also found that green banking has a decisive role in improving the financial performance of banks in countries. The results of Hossain et al (2020), Shaumya and Arulrajah (2016), Karyani and Obrien (2020), Bose et al (2021), andPark andKim (2020) stated that green banking improves the performance of banks.…”
Section: Theoretical Principles and Hypothesis Developmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Khan et al (2021) showed that the disclosure of green banking has a positive and significant effect on the value of companies. Karyani and Obrien (2020), Bose et al (2021), and Park and Kim (2020) also found that green banking has a decisive role in improving the financial performance of banks in countries. The results of Hossain et al (2020), Shaumya and Arulrajah (2016), Karyani and Obrien (2020), Bose et al (2021), andPark andKim (2020) stated that green banking improves the performance of banks.…”
Section: Theoretical Principles and Hypothesis Developmentmentioning
confidence: 98%
“…Karyani and Obrien (2020), Bose et al (2021), and Park and Kim (2020) also found that green banking has a decisive role in improving the financial performance of banks in countries. The results of Hossain et al (2020), Shaumya and Arulrajah (2016), Karyani and Obrien (2020), Bose et al (2021), andPark andKim (2020) stated that green banking improves the performance of banks. Bhattrai (2017) addressed the impact of corporate governance on bank performance in Nepal.…”
Section: Theoretical Principles and Hypothesis Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Sementara itu, kepemilikan asing melemahkan pengaruh positif praktik perbankan hijau terhadap nilai perusahaan. Dengan demikian, para pemangku kepentingan dapat mempertimbangkan praktik perbankan hijau tersebut dalam pembuatan keputusan keuangan mereka karena faktor tersebut mempengaruhi kinerja bank (Karyani & Obrien, 2020). H1: Green Financing berpengaruh positif signifikan terhadap profitabilitas Bank Syariah…”
Section: Green Finance Terhadap Profitabilitasunclassified
“…Robust findings also highlights political connections of banks negatively affects this relationship. Karyani and Obrien (2020) examine the effect of green banking practice on bank performance with foreign and public ownership as moderating variables of 14 Indonesian banks with 98 bank year observations between 2012 and 2018. By applying OLS (ordinary least square) model, this study provides useful insights that green banking practices have a negative impact on bank profitability but a positive impact on firm value.…”
Section: Related Literature Reviewmentioning
confidence: 99%